Phosphorylation of the rev gene product of human immunodeficiency virus type 1. - Hauber, J (1988)
Replication of human immunodeficiency virus type 1 requires the functional expression in trans of the virally encoded rev gene product (previously called art/trs). Here we demonstrate that this protein can be metabolically labeled with 32Pi. The phosphate receptor in the rev protein is shown to be exclusively serine. Treatment of rev-expressing cells with phorbol ester, a specific activator of protein kinase C, led to significant but transient enhancement of the level of rev phosphorylation. These results indicate that the rev protein is posttranslationally modified in vivo and suggest that the level of this modification is subject to modulation by extracellular stimuli.